2021
DOI: 10.3390/su132212909
|View full text |Cite
|
Sign up to set email alerts
|

Linking the Development of Building Sustainability Assessment Tools with the Concept Evolution of Sustainable Buildings

Abstract: With the rapid development of materials science and construction technology, the concept of sustainable building (SB) and the Building Sustainability Assessment Tool (BSAT) have also evolved and developed. Understanding the development of BSAT and SB is of great significance to the sustainable development of the construction industry. This research used the bibliometric method to analyze the development and evolution in the relevant literature on SB and BSAT from 1990 to 2021, and the correlations and differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 157 publications
0
2
0
Order By: Relevance
“…Moreover, a study by Liang et al reviewed and analysed the evolution in the literature on sustainable building and sustainable assessment tools from 1990 to 2021 and critically concluded that there are deficiencies in the used research methods of studying the building sustainable assessment tools, as most of the reviewed studies had not developed a unified assessment framework for different tools resulting in insufficient accuracy [149].…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…Moreover, a study by Liang et al reviewed and analysed the evolution in the literature on sustainable building and sustainable assessment tools from 1990 to 2021 and critically concluded that there are deficiencies in the used research methods of studying the building sustainable assessment tools, as most of the reviewed studies had not developed a unified assessment framework for different tools resulting in insufficient accuracy [149].…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…The bioclimatic theory is based on local architecture and observes the specific environmental characteristics of buildings. In this optimal manner, the construction industry can operate cost-effectively and sustainably [33][34][35]. Traditional residential buildings in India's composite climate [36,37], Yaodong dwellings in China's Loess Plateau region [38,39], and stilt houses in tropical regions such as Thailand, Laos, Cambodia, Hawaii, and Guam are good examples of the implementation of this theory [40].…”
Section: Methodology 21 Theoretical Foundationsmentioning
confidence: 99%
“…In addition, there are various factors that affect the energy efficiency of courtyard buildings [25][26][27][28][29][30]. Shashua-Bar and Hoffman [31] lowered the temperature inside the building by increasing the height of the building and deepening the adjoining courtyard.…”
Section: Literature Review 21 Traditional Courtyard Model and Its Ene...mentioning
confidence: 99%